Analyzing “Learn Arabic for Beginners” TikTok Content Based on the CEFR: تحليل محتوى تعليم اللغة العربية على تطبيق تيك توك في ضوء الإطار الأوربي المشترك للغات: “Learn Arabic for Beginners” أنموذجا - Dita Puspita Dewi; Gita Putri Ramadhani; Asep Sopian (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to evaluate the Arabic language learning content featured on the TikTok account “Learn Arabic for Beginners” about the Common European Framework of Reference for Languages (CEFR), specifically targeting A1–A2 levels for beginner learners. Additional objectives include assessing the extent to which the content aligns with linguistic competencies (vocabulary, phonology, grammar) and language activities (reception, production, interaction, and mediation) as outlined by the CEFR descriptors. The study used a content analysis method with a descriptive qualitative approach, using purposive sampling to select highly interacted videos for in-depth analysis. The findings indicate that the majority of the content complies with A1–A2 proficiency levels, particularly demonstrating clear mastery of phonological elements and basic vocabulary. The platform supports receptive and productive language activities effectively. However, the interactive and mediational components remain underdeveloped and could be improved through features such as duet videos, live sessions, and audience engagement in comments. This research contributes theoretically to digital Arabic language pedagogy aligned with CEFR standards. It offers practical insights for educators and content creators to design more structured, engaging, and level-appropriate learning materials for beginner Arabic learners.